1987
DOI: 10.1104/pp.83.4.941
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Leaf Senescence and Correlatively Controlled Increases in Xylem Flow Resistance

Abstract: In bean, Phaseolus vulgaris L. (Contender), the directly measured hydraulic resistance of the xylem pathway between roots and primary leaf pulvinal junctions increased rapidly and progressively from 21 to 28 days after planting. These increases in xylem resistance (+390%) were specifically located in the pulvinal junction of the primary leaf. Moreover, they occurred just prior to the onset of primary leaf yellowing. Developmental increases in xylem hydraulic flow resistance and stomatal resistance, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…Schultz & Matthews (1993) found that the conductivity per xylem cross-sectional area increases by an order of magnitude during the period of leaf expansion in grape. Neumann (1987) found pulvinar xylem conductivity decreases four-fold during senescence of bean leaves. In general, a possible explanation for the small effect of xylem diameter on hydraulic conductivity is that the conductivity in mature leaves is affected less by the diameter of xylem elements of the growth zone than by hydraulic bottlenecks -constriction zones in roots, stems or leaf blades.…”
Section: mentioning
confidence: 99%
“…Schultz & Matthews (1993) found that the conductivity per xylem cross-sectional area increases by an order of magnitude during the period of leaf expansion in grape. Neumann (1987) found pulvinar xylem conductivity decreases four-fold during senescence of bean leaves. In general, a possible explanation for the small effect of xylem diameter on hydraulic conductivity is that the conductivity in mature leaves is affected less by the diameter of xylem elements of the growth zone than by hydraulic bottlenecks -constriction zones in roots, stems or leaf blades.…”
Section: mentioning
confidence: 99%
“…However, it seems that the rapid wall responses described here can be initiated by hydraulic signals alone. This is not a unique example of such signaling; longdistance hydraulic signals have also been invoked in control of stomatal closure, sequential leaf senescence, stem elongation, and rapid systemic responses to wounding (Raschke, 1970;Neumann, 1987;Nonami and Boyer, 1990a;Malone, 1992). Moreover, even hormonal messages, e.g.…”
Section: Signaling Processesmentioning
confidence: 99%
“…The signaling process by which PEG treatment of roots induces cell-wall hardening in relatively distant leaves was also investigated. Possible involvement of hydraulic (Neumann, 1987;Kramer, 1988;Boyer, 1990a), hormonal (Saab andSharp, 1989;Davies and Zhang, 1991;Tardieu et al, 1993) and electrical (Pickard, 1973;Malone, 1992;Stahlberg and Cosgrove, 1992) signaling was considered: The relative importance of the different signals was evaluated by detennining leaf responses to PEG applied to live or killed roots. Killed roots responded hydraulically but were presumed unable to generate electrical or hormonal signals.…”
mentioning
confidence: 99%
“…In most of the work reported by other authors, purified bacterial polysaccharides (see Corey & Starr 1957) or artificially synthesized polymers were applied to elucidate the mechanisms of phytopathogenicity. The effects of polysaccharides on ornamental cut flowers, however, have rarely been studied (Hodgson et al 1949;Van Alfen & Turner 1975;Van Alfen & Allard-Turner 1979;Van Alfen et al 1983;de Stigter & Broekhuysen 1986;Neumann 1987). In the present work, molecular filtrates and retentates of supernatant fluids of pure cultures of several micro-organisms grown in an agitated sucrose-containing medium were used as a vase medium for cut roses cv.…”
mentioning
confidence: 87%
“…Reports of levan-forming Bacillus and Pseudomonas species are mentioned by Sutherland (1977Sutherland ( , 1979 and by Powell (1979). Most of the organisms used in our experiments are known commonly to form exopolysaccharides (possibly levans) (Wilkinson 1958(Wilkinson , 1977Gorin & Spencer 1968;Govan et al 1979;Powell 1979;Anderson 1984;Marques et al 1986;Neumann 1987).…”
Section: P O L Y S a C C H A R I D E F O R M A T I O Nmentioning
confidence: 99%